The association of different auto-antibodies against ovarian tissues and gonadotropins and poor ovarian response in intracytoplasmic sperm injection cycles. (3rd April 2017) - Mohammadi Yeganeh, Ladan; Moini, Ashraf; Hemmat, Mandana; Salman Yazdi, Reza; Bagheri Lankarani, Narges; Khodabakhshi, Shabnam; Behbahanian, Arash
Abstract: This study aimed to assess the possible association between ovarian auto-antibodies and poor ovarian response to controlled ovarian hyperstimulation (COH) in patients undergoing intracytoplasmic sperm injection (ICSI) cycles. In total, 42 poor responders and 43 male factor subjects were enrolled in the study and underwent either a standard long gonadotropin-releasing hormone (GnRH) agonist or antagonist protocol. Anti-ovarian, anti-oocyte, anti-zona pellucida (anti-ZP) and anti-gonadotropin antibodies in their sera and follicular fluid (FF) were measured by an enzyme-linked immunosorbent assay technique (ELISA). The mean follicular fluid anti-oocyte antibody [ratio of optical density (OD)sample /ODControl ] was significantly higher in poor responders compared to the normal group (2.40 ± 1.55 versus 1.72 ± 0.71, p  = 0.012). The linear regression analysis showed an inverse correlation between FF anti-oocyte antibody concentrations and the number of: (i) retrieved oocytes ( B = −1.212, r = −0.235, p  = 0.030); (ii) mature oocytes ( B = −1.042, r = −0.234, p  = 0.031); (iii) embryos available ( B = −0.713, r = −0.228, p  = 0.036); and (iv) good quality embryos ( B = −0.369, r = −0.229, p  = 0.035). However, there were no significant differences between two groups in terms of FF and serum anti-ovarian, anti-gonadotropins and anti-ZP antibodies. The Pearson correlation analysis on 85 infertile patients showed a positive correlation between age and the levels of FF anti-oocyte antibody ( r  = 0.276, p  = 0.010). This study demonstrated that FF anti-oocyte antibody could be associated with poor response to COH in ICSI cycles.